Hypoglycemic effect of the leaves of pandisho (artocarpus altilis) in aloxanized rats - Escobedo-Bailón, Christian M. (2019)
The objective of the present research was to verify the hypoglycemic pharmacological action of ethanolic extracts of leaves of Artocarpus altilis in aloxanized rats.An experimental study was carried out with 80 laboratory rats maintained in the biotery of the Faculty of Veterinary Medicine and Zootechny of the National University Hermilio Valdizán from Huánuco during the period 2016. The animals were divided into 4 groups of 20 rats each, of wich three groups was Experimental and received the ethanolic extracts in concentration of 25%, 50% and 75% respectively and one positive control group of animals treated with Glibenclamide®. The data were obtained through an observation guide. We used the ANOVA, Tukey and Bonferroni tests respectively. After treatment in experimental group 3 (75% concentration of ethanolic extracts) at 30 minutes, 6 hours, 18 hours and 36 hours a mean glucose decrease of 188.6 was obtained; 158.3; 130.1 and 108.6 mg / dl, respectively. In contrast, in experimental group 1 (25% concentration of ethanolic extracts), experimental group 2 (concentration 50% of ethanolic extracts) and control group (Glibenclamide®) where the glucose averages did not decrease. These results were statistically significant (p≤0,000).Concluding that the leaves of the pandisho (Artocarpus altilis) have hypoglicemic action.